Tajik Coaches' experiences in a sport for development program using systems theory: a longitudinal investigation - Blom, Lindsey C.; Hilliard, Robert C.; Gerstein, Lawrence H.; Judge, Lawrence; Vasiloff, Olivia; Ballesteros, Jorge; Johnson, James E. (Managing sport and leisure, 2024)
We used systems theory with the structural, attitudinal, and transactional (SAT) model of peace building to explore coaches' process and content of change after receiving sport for development and peace (SDP) training in Tajikistan. Six Tajik grassroots youth coaches from the Sport for Social Change Tajikistan (SSC-T) program participated in data collection over a four-year span. A longitudinal participatory approach utilizing interviews, journals, and guided discussion was analyzed using content analysis. Data indicated that in early stages of the program, micro-attitudinal changes were being made by the participants, with more transactional changes over time with a hint of structural, macro-level changes in the schools and community at the four-year mark. More specifically, we identified five themes across time: (1) girls' involvement, (2) positive coaching approaches, (3) incorporation of peaceful living skills, (4) cultural awareness, and (5) collaboration and community impact. Results revealed that over time participants moved from micro-level individual change to more structural level change in local Tajik communities; thus, providing evidence for the SAT model of peace building as a framework (Ricigliano, 2012. Making peace last: A toolbox for sustainable peacebuilding. Routledge).